Manajemen Strategik Rumah Sakit: Sebuah Tinjauan - Purwadhi, Purwadhi; Widjaja, Yani Restiani; Witarsih, Silvia; Wentinusa, Stella Maria (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
Strategic management of hospitals is becoming increasingly important in the dynamic healthcare industry. Hospitals are faced with challenges such as managing limited resources, policy changes, and evolving patient needs. To achieve competitive advantage, hospitals need to adopt best practices in strategic management. This study discusses the concept and practice of hospital strategic management through a literature review. It aims to identify strategies that hospitals can implement to improve operational efficiency, service quality, and patient satisfaction. In addition, this study also analyzes the challenges and opportunities faced by hospital management in formulating and implementing effective strategies, as well as identifying best practices that can be adopted to achieve competitive advantage in the healthcare industry. The results showed that hospitals can implement strategies such as the use of Balanced Scorecard (BSC) and EFQM models, training for hospital managers, and integration of information technology. In addition, strong collaboration with stakeholders and human resource development are also important factors. This study concludes that strategic management of hospitals requires a holistic and integrated approach. By adopting best practices, hospitals can improve their performance, meet patient expectations, and contribute to the overall improvement of public health.